2020
DOI: 10.1080/03081087.2020.1862742
|View full text |Cite
|
Sign up to set email alerts
|

Decompositions of matrices into diagonalizable and square-zero matrices

Abstract: For any n ≥ 2 and fixed k ≥ 1, we give necessary and sufficient conditions for an arbitrary nonzero square matrix in the matrix ring Mn(F) to be written as a sum of an invertible matrix U and a nilpotent matrix N with N k = 0 over an arbitrary field F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The construction is based on Jordan blocks and roots of unity. Let us consider the explicit decomposition for a Jordan block (see Remarks 2.8 and 2.9 from [8]).…”
Section: Decomposition Into Potent Matrix and Zero-square Matrix Over Algebraically Closed Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction is based on Jordan blocks and roots of unity. Let us consider the explicit decomposition for a Jordan block (see Remarks 2.8 and 2.9 from [8]).…”
Section: Decomposition Into Potent Matrix and Zero-square Matrix Over Algebraically Closed Fieldsmentioning
confidence: 99%
“…Since K is algebraically closed and A is similar to a direct sum of Jordan blocks then it is sufficient to decompose each Jordan block. Let J be a Jordan block of size m × m for some m n and q is the characteristic of K. If m 2 the decomposition is straightforward (see Section 1 of [8]). When m 3 and if q does no divide m then decomposition of J is presented in Lemma 2.1(i).…”
Section: Decomposition Into Potent Matrix and Zero-square Matrix Over Algebraically Closed Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief collection of principally known historical facts in this branch are as follows: In [6] was shown that any square matrix over the finite two elements field Z 2 is a sum of a nilpotent matrix and an idempotent matrix; thereby the full matrix n × n ring M n (Z 2 ) is called nil-clean. This important fact was strengthened in [23] by showing that, for any n ∈ N and for every n × n matrix A over Z 2 , there exists an idempotent matrix E such that (A − E) 4 = 0, while over the finite indecomposable ring Z 4 consisting of four elements this relation is precisely (A − E) 8 = 0 (see [2] and [22] for some further generalizations and specifications, too). In [23] is showed also that the ring ∞ n=1 M n (Z 2 ) is both nil-clean and von Neumann regular but not strongly π-regular, whereas the ring ∞ n=1 M n (Z 4 ) is both nil-clean and regularly nil clean but not π-regular (see [9], as well).…”
Section: Introduction and Fundamentalsmentioning
confidence: 99%
“…The aim of this short article is to settle this conjecture in the case of algebraically closed fields. This will be successfully done in the sequel (compare with [12] and [8] as well). Further eventual applications of such decompositions could be realized in coding theory and, in particular, in noncommutative coding theory (cf.…”
Section: Introduction and Fundamentalsmentioning
confidence: 99%